EVOLUTION OF TETHYAN PHOSPHOGENESIS ALONG THE NORTHERN EDGES OF THE ARABIAN-AFRICAN SHIELD DURING THE CRETACEOUS-EOCENE AS DEDUCED FROM TEMPORAL VARIATIONS OF CA AND ND ISOTOPES AND RATES OF P ACCUMULATION - Soudry D.; Nathan Y.; Segal I.; Glenn C.R.; VonderHaar D. (My University, 2006)
The evolution of Tethyan phosphogenesis during the Cretaceous-Eocene is examined to try to explain fluctuations of phosphogenesis through time, and whether or not they reflect long-term changes in ocean circulation or in continental weathering. Twenty-seven time-stratigraphic phosphate levels in various Tethyan sites, covering a time span of about 90 Myr from the Hauterivian to the Eocene, were analyzed for 44Ca/42Ca and 143Nd/144Nd in their carbonate fluorapatite (CFA) fraction. P and Ca accumulation rates and bulk sedimentation rates were quantified throughout the Cretaceous-Eocene Negev sequence to examine how changes in 44Ca/42Ca and 143Nd/144Nd are reflected in the intensity of phosphogenesis. A clear-cut change occurs in εNd(T) and δ44Ca and in the rates of P and Ca accumulation and bulk sedimentation through the time analyzed. εNd(T) is much lower in the Hauterivian-Lower Cenomanian (- 12.8 to - 10.9) than in the Upper Cenomanian-Eocene (- 7.8 to - 5.9). Much lower δ44Ca values occur in the Hauterivian-Turonian (- 0.22 to + 0.02) than in the Coniacian-Eocene (+ 0.23 to + 0.40). P accumulation rates in the Negev steeply increase from < 200 μmol cm- 2 k yr- 1 in the Albian-Coniacian to ~ 1500 μmol cm- 2 k yr- 1 in the Campanian, whereas a strong decrease is concomitantly recorded in the rates of Ca accumulation and bulk sedimentation. In addition, distinct εNd(T) values are shown by the phosphorites of the Negev (- 6.7 to - 6.4) and Egypt (- 9.1 to - 7.6) during the Campanian, and by those of the Negev (- 7.8 to - 6.3) and North Africa (- 10.1 to - 8.9) during the Maastrichtian-Eocene. The culmination of P accumulation rates in the Negev during the Campanian, occurring with a high in εNd(T) and δ44Ca and a low in sedimentation rates, indicates that paleoceanographic and paleogeographical factors mostly governed phosphorite accumulation in this area. The abrupt εNd(T) rise after the Cenomanian is attributed to increased incursion of Pacific (radiogenic) water masses into the Tethys, driven by the Late Cretaceous global sea-level rise, the connection between North and South Atlantic, the global post-Santonian cooling, and the progressive widening of the Caribbean threshold, all acting in combination to significantly intensify the Tethyan circumglobal current (TCC). It also reflects a weakening of the continental Nd signal due to a reduction of exposed landmasses caused by increased flooding of continental shelves. High δ44Ca values at those times also point to a decrease in weathering Ca+2 fluxes and expansion of carbonate sedimentation in shelves, both enriching seawater with isotopically heavy Ca+2. Deep ocean circulation intensified by the post-Santonian cooling of high latitudes increased P inventory in the Tethys basin, whereas the strengthened TCC and the folded shelf likely resulted in coastal and topographically-induced upwelling, supplying P-rich intermediate waters to southeastern Tethys shelves. Only in the Paleocene-Eocene, following major changes in global circulation produced by narrowing of Tethys and widening of the Atlantic, did phosphogenesis shifts its locus of high intensity to the western (Atlantic) Tethys and West African Atlantic coasts. This change in paleocirculation is expressed by distinctly differing εNd(T) in the Middle East and the North and West African phosphorites, suggesting different oceanic P sources and current systems for these two major groups of phosphorites. Our Nd isotope results further suggest a weaker TCC during the Mid-Cretaceous, becoming more intense in Late Cretaceous times. They also point to the North Pacific Ocean as major source of deep water formation for the intermediate-deep waters in the Tethys Basin during the Late Cretaceous. © 2006 Elsevier B.V. All rights reserved.
Keywords: δ44/42CA; εND(T); CRETACEOUS-EOCENE; DEEP WATER FORMATION; P ACCUMULATION RATES; PALEOCEANOGRAPHY; PHOSPHOGENESIS; SOUTH TETHYS MARGINS; TCC; Кайнозой::Палеоген::Эоцен; Кайнозой::Палеоген::Палеоцен; Мезозой::Меловая::Верхний::Маастрихтский; Мезозой::Меловая::Верхний::Кампанский; Мезозой::Меловая::Верхний::Сантонский; Мезозой::Меловая::Верхний::Коньякский; Мезозой::Меловая::Верхний::Туронский; Мезозой::Меловая::Верхний::Сеноманский; Мезозой::Меловая::Нижний::Альбский; Мезозой::Меловая::Нижний::Готеривский; Cenozoic::Paleogene::Eocene; Cenozoic::Paleogene::Paleocene; Mesozoic::Cretaceous::Upper::Maastrichtian; Mesozoic::Cretaceous::Upper::Campanian; Mesozoic::Cretaceous::Upper::Santonian; Mesozoic::Cretaceous::Upper::Coniacian; Mesozoic::Cretaceous::Upper::Turonian; Mesozoic::Cretaceous::Upper::Cenomanian; Mesozoic::Cretaceous::Lower::Albian; Mesozoic::Cretaceous::Lower::Hauterivian